Repercussões das vivências com pesquisa na formação integral de estudantes da educação profissional técnica de nível pós-médio em química - Menegasso, Paulo José (2017)
Nowadays, reflecting on education and learning requires recognizing that information and communication technologies are changing in different spheres of society. It places itself as a need to revise educational projects, redefining the training of subjects to respond to contemporary issues. Teachers and managers are today tense between the certainty that the traditional model of teaching needs to be overcome and the search for proposals for the formation of the subject in society. What learning is essential to live and act positively in contemporary society? What personal dimensions need to be developed? What teaching methodologies would account for the desired training? Thus the objective of the thesis is to understand the repercussions of the experiences in scientific activities in the integral formation of students of technical education in Chemistry. This thesis is justified to understand the meanings of the research in the development of students of a technical course in chemistry of a high school in a state public institution, scientific education as competences. The research projects were produced based on the precepts of educating by research, with theoretical references of Pedro Demo (2009), and Galiazzi (2011). The methodology consisted of two phases. The first part was a documentary study aimed at evaluating the quality of research projects between 2009 and 2013. The second phase consisted of a qualitative case study, using three focus groups totaling 15 subjects and nine Descriptive memorials. In this phase we used the Discursive Textual Analysis for analysis, based on Moraes and Galiazzi (2014), in order to understand the meanings of the research that influence future activities of the students. For data collection, three a priori questions were defined in order to facilitate the understanding of meanings, such as the procedures with the research that contributed most to the students' education, the repercussions of the activities with research in the professional and personal formation. This aim was to answer what were the repercussions of the experiences in scientific activities in the integral formation of the students of professional education of medium technical level in Chemistry? The results of phase 1 are presented as an activity that contributes to learning and scientific education. The results of phase 2 indicate that the process of scientific education with research changes the role of subjects by placing the student at the center of the activity to construct and reconstruct their arguments. The work with the research implies reading, writing and interpretation in which the focus is not the result, but rather the process, in which the subjects with intrinsic motivation present new arguments in a never completed process. The results indicate that the students become more critical, performing a reconstructive questioning. It is concluded that experiences in scientific activities with student-centered research projects promote learning by making subjects more critical and responsible, both as technicians and as undergraduates, making possible positive repercussions of becoming critical citizens with autonomy of writing and argumentation and interacting and looking the world with the eyes of science.